Pattern and Prevalence of Rheumatic Heart Disease by Echocardiographic Evaluation - Shah, R.K.; Upadhayaya, A.B.; Tibrewala, L.P.; Regmi, P.R.; Acharya, K.P.; Khanal, H.H. (Nepalese Heart Journal, 2003)
The pattern of cardiac disease differs from one region of the world to that of another. Rheumatic heart disease Is still widely prevalent in Nepal. The patterns and natural history is considerably different from what is seen in developed countries3, Few studies had been done in Nepal to address pattern of heart diseases4. Need of a large study to fill the gap and to show the profile of heart disease is there. This paper aims at providing the profile of heart disease as seen in Bir Hospital.